Quantitative appraisal of the Amyloid Imaging Taskforce appropriate use criteria for amyloid‐PET. Issue 8 (18th April 2018) - Altomare, Daniele; Ferrari, Clarissa; Festari, Cristina; Guerra, Ugo Paolo; Muscio, Cristina; Padovani, Alessandro; Frisoni, Giovanni B.; Boccardi, Marina; ,
Abstract: Introduction: We test the hypothesis that amyloid–positron emission tomography prescriptions, considered appropriate based on the Amyloid Imaging Taskforce (AIT) criteria, lead to greater clinical utility than AIT‐inappropriate prescriptions. Methods: We compared the clinical utility between patients who underwent amyloid–positron emission tomography appropriately or inappropriately and among the subgroups of patients defined by the AIT criteria. Finally, we performed logistic regressions to identify variables associated with clinical utility. Results: We identified 171 AIT‐appropriate and 67 AIT‐inappropriate patients. AIT‐appropriate and AIT‐inappropriate cases did not differ in any outcomes of clinical utility ( P  > .05). Subgroup analysis denoted both expected and unexpected results. The logistic regressions outlined the primary role of clinical picture and clinical or neuropsychological profile in identifying patients benefitting from amyloid–positron emission tomography. Discussion: Contrary to our hypothesis, also AIT‐inappropriate prescriptions were associated with clinical utility. Clinical or neuropsychological variables, not taken into account by the AIT criteria, may help further refine criteria for appropriateness.